2019
DOI: 10.17277/amt.2019.02.pp.019-024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbon Materials with Abnormally High Specific Surface Area

Abstract: As a rule, carbon materials with developed energy are produced by physical or active activation of carbon-containing precursor materials. Physical activation is usually carried out at a temperature of 800-900 °C. For chemical activation, many reagents have been proposed-phosphoric acid, zinc chloride, potassium sulfide, sodium hydroxide, potassium hydroxide, potassium carbonate, and others. All these techniques are aimed at increasing the specific surface and porosity of the original carbon nanomaterials. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…An even higher sorption capacity was demonstrated by a 2D carbon material. Melezhik et al [ 13 ] coated graphene oxide (GO) with various oxygen-containing groups and reported a high surface area. Zhao et al [ 14 ] described 106.3 and 68.2 mg/g sorption capacity of Cd (II) and Co (II) on graphene oxide at pH 6.0 ± 0.1 and T = 303 K. Wang et al [ 15 ] used ethylenediamine as a reducing agent and the obtained GO showed an adsorption capacity of 413.22, 162.33, 55.34 and 42.46 mg/g for Pb (II), Cd (II), Cu (II) and Mn (II), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…An even higher sorption capacity was demonstrated by a 2D carbon material. Melezhik et al [ 13 ] coated graphene oxide (GO) with various oxygen-containing groups and reported a high surface area. Zhao et al [ 14 ] described 106.3 and 68.2 mg/g sorption capacity of Cd (II) and Co (II) on graphene oxide at pH 6.0 ± 0.1 and T = 303 K. Wang et al [ 15 ] used ethylenediamine as a reducing agent and the obtained GO showed an adsorption capacity of 413.22, 162.33, 55.34 and 42.46 mg/g for Pb (II), Cd (II), Cu (II) and Mn (II), respectively.…”
Section: Introductionmentioning
confidence: 99%